Future local passenger transport system scenarios and implications for policy and practice. (May 2020) - Enoch, M.P.; Cross, R.; Potter, N.; Davidson, C.; Taylor, S.; Brown, R.; Huang, H.; Parsons, J.; Tucker, S.; Wynne, E.; Grieg, D.; Campbell, G.; et al.
Abstract: The world is rapidly changing and the future is uncertain, yet until recently the dominant assumption of the local passenger transport community has been that the existing modal landscape of cars, buses and taxis will remain much as it is now. Such a view is now shifting however, with decision makers now appreciating the need to understand the implications of potentially radical changes in the technological, political, economic, social and environmental spheres. Accordingly, in August 2015 the Public Transport 2045 study was commissioned to consider how different local public transport futures might affect society over the next 30-years, and at how governments might best respond. The multi-phase study was based on individual in-depth interviews with 50 senior local passenger transport operators, government officials, lobbyists and experts from New Zealand and around the world; and four validation workshops with 28 sector stakeholders. The data was analysed using mostly pre-determined themes from which four scenarios were constructed and then validated. The implications are that the local passenger transport system is about to transition to a system of 'shared mobility'; public transport will need to evolve to stay relevant but will remain important in any scenario; and the role of Government will be vital in overseeing the transition to the shared mobility era. These lessons are now being used to inform transport and broader policy decisions across New Zealand. Overall, the study is the first to apply such a global and qualitatively rich dataset to view the long-term future local passenger transport system as a whole. Highlights: - Considers passenger transport development over 30-years and Government response. - 50 interviews, 4 validation workshops (28 stakeholders) led to 4 future scenarios. - Public transport must evolve in transition to shared mobility future - Government has key function in overseeing the transition. - First large-scale, qualitative, long-term, global, holistic public transport study.